Implementasi Program Integrasi Pelayanan Kesehatan Primer (ILP) melalui Posyandu di Nagari Kasang - Putri, Mutiara; Adnan, M. Fachri (Lembaga Yasin AlSys, 2026)
Strengthening primary healthcare services through the Integrated Primary Healthcare Service Program (Integrasi Pelayanan Kesehatan Primer, ILP) constitutes a strategic component of the national health system transformation, aiming to improve access to and the quality of community-based health services across the life cycle. This study aims to analyze the implementation of ILP in Nagari Kasang, focusing on program execution, operational mechanisms, community participation, and the enabling and inhibiting factors affecting implementation effectiveness. A descriptive qualitative method was employed, with data collected through in-depth interviews, field observations, and documentation. Informants included health center staff, posyandu cadres, village government officials, and community service users. The findings indicate that the ILP implementation follows the Ministry of Health guidelines, yet faces several challenges, such as limited infrastructure, inadequate training for cadres, and suboptimal cross-sectoral coordination. Community participation is notably high among mothers and children but remains low among adolescents and the elderly. Based on David C. Korten’s implementation theory, the relationship between the program, implementing organization, and target groups reflects a partial fit, indicating a lack of synergy among the key actors. These findings highlight the need to enhance cadre capacity, strengthen the role of community health centers, and ensure active support from local government to achieve more effective and sustainable ILP implementation.